2011
DOI: 10.2147/ijn.s26070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heparan sulfate and gold nanoparticles on muscle development during embryogenesis

Abstract: Purpose It was hypothesized that heparan sulfate (HS) as an essential compound for myogenesis and nanoparticles of gold (nano-Au) as highly reactive compounds can affect muscle development as a consequence of molecular regulation of muscle cell formation, and that these effects may be enhanced by a complex of HS conjugated with nano-Au. The objective of the present study was to determine the effect of administration of nano-Au, HS, and a nano-Au+HS complex on the morphological and molecular charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…AgTANPs were prepared by mixing the heated aqueous solution of AgNO 3 (95.2 g, 0.017%) with the aqueous solution of tannic acid (0.6 g, 5% C 76 H 52 O 46 Sigma-Aldrich). The long-term stability of the colloidal dispersions of all tested NPs (zeta potential) was measured and confirmed by the electrophoretic lightscattering method with a Zetasizer Nano ZS, model ZEN3500 (Malvern Instruments, Worcestershire, UK) (Orlowski et al 2014;Urbańska et al 2015;Zielinska et al 2011).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…AgTANPs were prepared by mixing the heated aqueous solution of AgNO 3 (95.2 g, 0.017%) with the aqueous solution of tannic acid (0.6 g, 5% C 76 H 52 O 46 Sigma-Aldrich). The long-term stability of the colloidal dispersions of all tested NPs (zeta potential) was measured and confirmed by the electrophoretic lightscattering method with a Zetasizer Nano ZS, model ZEN3500 (Malvern Instruments, Worcestershire, UK) (Orlowski et al 2014;Urbańska et al 2015;Zielinska et al 2011).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…The hydrocolloids of silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs) were produced by an electric non-explosive method from high purity metals and demineralized water (Polish Patent 380649) obtained from Nano-Tech, Warsaw, Poland. The long-term stability of the colloidal dispersions of all tested NPs (zeta potential) was measured and confirmed by electrophoretic light-scattering method with a Zetasizer Nano ZS, model ZEN3500 (Malvern Instruments, Worcs., UK) [21,22]. The well-dispersed nanofluids were used as a stock solution and appropriately diluted to various nanoparticles concentrations (ppm), ranging between 0.25-2.5 ppm, and used in subsequent assays of the cytotoxicity and anti-amoebic activity.…”
Section: Acanthamoeba Strain Included -Molecular Identification and Cmentioning
confidence: 99%
“…Actc1 is up ∼ 2 fold in vascular smooth muscle in mice lacking Ndst1 . Previous work has shown that heparan sulfate does alter muscle development [62]. Actn2 , is also found primarily in skeletal muscle and heart.…”
Section: Discussionmentioning
confidence: 99%